Impact of new generations drug-eluting stents overlap on six-month clinical outcomes in patients with acute anterior STEMI treated with primary PCI. (25th November 2020) - Elakabawi, K; Shah, S.A; Fadlullah, H; Yuan, Z.Y; Guo, N
Abstract: Background: Stent overlap has been associated with adverse outcomes. However, data regarding the impact of new generations drug-eluting stents (DES) overlap in the context of ST-segment elevation myocardial infarction (STEMI) are limited. Objective: To compare the 6-moth clinical outcomes of patients with and without new generations DES overlap implanted during primary PCI for anterior STEMI. Methods: We evaluated a total of 1078 consecutive anterior STEMI patients who underwent primary PCI with deployment of new generations DES. The patients were divided according to the presence or absence of stent overlap into 2 groups; overlapping-stents group (n=388) and single-stent group (n=690). We compared the rates of cardiac mortality, major adverse cardiovascular events (MACEs; composite of death, reinfarction, ischemia-driven target vessel revascularization (TVR), definite stent thrombosis (ST), and stroke) between the 2 groups. Results: There was a non-significant trend toward increased in-hospital mortality in the overlapping-stents group related to a significant higher rate of cardiogenic shock [9.5% versus 6.1%, respectively; P=0.037] and post-procedural suboptimal TIMI flow [26.3% versus 19.4%, respectively; P=0.009] as compared to the single-stent group. Yet, there were no significant differences between the 2 groups in the incidence of 6-month cardiac death: [18 (4.6%) and 21 (3%); P=0.173], MACEs: [35 (9%) and 49 (7.1%); P=0.259], reinfarction: [14 (3.6%) and 22 (3.2%); P=713], TVR: [17 (4.4%) and 28 (4.1%); P=0.799], and definite ST: [14 (3.6%) and 19 (2.8%); P=0.434], respectively. Conclusion: The use of multiple overlapping new generations DES, if needed, is relatively safe and acceptable in the context of primary PCI for STEMI patients. Funding Acknowledgement: Type of funding source: None